Gut Microbial Characteristics of Adult Patients With Epilepsy - Dong, Lian; Zheng, Qian; Cheng, Yongran; Zhou, Mengyun; Wang, Mingwei; Xu, Jianwei; Xu, Zucai; Wu, Guofeng; Yu, Yunli; Ye, Lan; Feng, Zhanhui (Frontiers in Neuroscience, 2022)
To characterize the intestinal flora of patients with epilepsy and its correlation with epilepsy. Methods：Patients with ages > 18 years were consecutively enrolled from the outpatient department, Affiliated Hospital of Guizhou Medical University from January 2018 to December 2019. A total of 71 subjects were recruited, including epilepsy patients (n = 41) as an observation group and patient family members (n=30) as a control group. Fresh stool specimens of all the subjects were collected. The 16S ribosomal RNA sequencing was analyzed to determine changes in intestinal flora composition and its correlation with epilepsy. Subgroup analysis was then conducted. All patients with epilepsy were divided into an urban group (n=21) and a rural group (n=20) according to the region, and the bioinformatics analyses were repeated between subgroups. Results: LEfSe analysis showed that Fusobacterium, Megasphaera, Alloprevotella, and Sutterella had relatively increased abundance in the epilepsy group at the genus level. Correlation analysis suggested that Fusobacterium sp. (r=0.584, P˂ 0.01), Fusobacterium mortiferum (r=0.560, P˂0.01), Ruminococcus gnavus (r=0.541, P<0.01), and Bacteroides fragilis (r=0.506, P<0.01) were significantly positively correlated with the occurrence of epilepsy (r≥0.5, P<0.05). PICRUSt function prediction analysis showed that there were significant differences in 16 pathways between the groups at level 3. Comparing the rural group with the urban group, Proteobacteria increased at the phylum level and Escherichia coli, Fusobacterium varium, Prevotella stercorea, and Prevotellaceae bacterium DJF VR15 increased at the species level in the rural group. Conclusions：There were significant differences in the composition and functional pathways of gut flora between epilepsy patients and patient family members. The Fusobacterium may become a potential biomarker for the diagnosis of epilepsy.